Predicting Islamic Banks Performance During the Covid-19 Pandemic through CAMEL Ratio Strategy - Siti Fitriyah; Happy Sista Devy; Muhammad Aris Safii; Norma Alias (Cahaya Abadi Publisher, 2022)
The Covid-19 pandemic, which has spread to almost all countries in the world, is currently causing the social and economic life of the community to shake so that it is thought to affect the financial performance of Islamic banks. This study aims to determine the financial performance of Islamic banks before and during a pandemic. The study was conducted by comparing financial reports with CAMEL analysis. The results of the study show that there is no significant difference between the financial performance of Islamic banks before and during the outbreak. Despite the global crisis due to the Covid-19 pandemic, the financial performance of Islamic banks has remained stable. This can be seen in the increase in financial ratios such as CAR and ROA, while the BOPO and NPF ratios tend to decrease, which indicates the efficiency of funds operated by the bank. Even though there was an increase in the amount of credit issued, the increase was still safe.